Sedimentation study of the Yazoo River Basin. Phase I, Temporal design - Simons, D. B., author; Li, R. M., author; Ward, T. J., author; Duong, N., author; Civil Engineering Department, Engineering Research Center, Colorado State University, publisher (Colorado State University. Libraries, 1978)
The purpose of this investigation is to determine the extent of sediment problems in the main stem Yazoo-Tallahatchie-Coldwater River System and principal tributaries excluding the Sunflower River Basin. In addition, this study recommends ways to control these sedimentation problems and others that may be encountered with the proposed Upper Auxiliary Channel Alternative Project in operation. This report details techniques for developing discharge records for the Yazoo River Basin Sedimentation Study.
CER77-78 DBS-RML-TJW-ND49.
Prepared for U.S. Army Corps of Engineers, Vicksburg District, Vicksburg, Mississippi.
June 1978.
Keywords: Sedimentation and deposition -- Mississippi -- Yazoo River